2020
DOI: 10.1097/mnm.0000000000001314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 81mKrypton and 99mTc-Technegas for ventilation single-photon emission computed tomography in severe chronic obstructive pulmonary disease

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Technegas is an ultrafine aerosolized particle (0.005-0.2 μm (Lemb et al, 1993)) whose distribution in the lungs, unlike that of 129 Xe gas, is impacted by aerosol deposition mechanics. While Technegas behaves in a gas-like manner, permitting peripheral penetration and alveolar deposition (Bajc et al, 2019), it has been previously shown to aggregate at sites of severe obstruction leading to "hot-spots" (De Nijs et al, 2021). Shown in Figure 1D, we observed this effect in a 65-year-old male with severe COPD (FEV 1 = 28% pred , FEV 1 / FVC = 31%).…”
Section: Figuresupporting
confidence: 52%
“…Technegas is an ultrafine aerosolized particle (0.005-0.2 μm (Lemb et al, 1993)) whose distribution in the lungs, unlike that of 129 Xe gas, is impacted by aerosol deposition mechanics. While Technegas behaves in a gas-like manner, permitting peripheral penetration and alveolar deposition (Bajc et al, 2019), it has been previously shown to aggregate at sites of severe obstruction leading to "hot-spots" (De Nijs et al, 2021). Shown in Figure 1D, we observed this effect in a 65-year-old male with severe COPD (FEV 1 = 28% pred , FEV 1 / FVC = 31%).…”
Section: Figuresupporting
confidence: 52%